2019
DOI: 10.1089/dia.2018.0264
|View full text |Cite
|
Sign up to set email alerts
|

Safety Evaluation of the MiniMed 670G System in Children 7–13 Years of Age with Type 1 Diabetes

Abstract: Objective: To evaluate the safety of in-home use of the MiniMedÔ 670G system with SmartGuardÔ technology in children with type 1 diabetes (T1D). Methods: Participants (N = 105, ages 7-13 years, mean age 10.8-1.8 years) were enrolled at nine centers (eight in the United States and one in Israel) and completed a 2-week baseline run-in phase in Manual Mode followed by a 3-month study phase with Auto Mode enabled. Sensor glucose (SG), glycated hemoglobin (HbA 1c), percentage of SG values across glucose ranges, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
113
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 164 publications
(138 citation statements)
references
References 43 publications
22
113
1
2
Order By: Relevance
“…Likewise, each 8.6‐h increase in Auto Mode time per day was associated with 5% more TIR. These findings are consistent with previous 670G trials that demonstrated improvements in glycaemia, including increased TIR and reduction in HbA1c . The ability of automated insulin delivery to improve glycaemia may particularly benefit adolescents and young adults, who have mostly struggled with meeting therapeutic targets.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Likewise, each 8.6‐h increase in Auto Mode time per day was associated with 5% more TIR. These findings are consistent with previous 670G trials that demonstrated improvements in glycaemia, including increased TIR and reduction in HbA1c . The ability of automated insulin delivery to improve glycaemia may particularly benefit adolescents and young adults, who have mostly struggled with meeting therapeutic targets.…”
Section: Discussionsupporting
confidence: 90%
“…In conclusion, whereas the MiniMed 670G system has demonstrated the potential to improve glycaemic outcomes, our findings suggest that these improvements are diminished when time spent in HCL is limited by frequent Auto Mode exits. In our clinical practice and other recently published cohorts, time spent in Auto Mode is substantially lower than in previously published trials . Future automated insulin delivery systems that reduce the burden of staying in the closed‐loop mode have the potential to enhance glycaemic control substantially in the paediatric and adolescent T1DM population.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations